Sistema de numeração decimal na formação continuada de professores em serviço que ensinam matemática nos primeiros anos do ensino fundamental: o caso da secretaria municipal de educação do município de Maracanã/Pa - CARRÉRA, Gerson Luíz de Carvalho (Universidade Federal do Pará, 2021)
The main objective of this research in teacher education is to investigate the contributions of the study on Decimal Numbering System (SND), considering its History and Epistemology, for teachers in exercise who teach Mathematics in the first years of elementary school in the municipality of Maracanã/PA. The main theoretical references are Lerner and Sadovsky (1996), Kamii (1996), Nogueira (2011), Curi (2013) and Ferreira, Guerra and Viana (2019). This work with a formative perspective is a workshop, composed of four meetings, offered to 19 teachers who work in the municipal public school system of Maracanã-PA, located in the northeast of the Amazon of Pará. To achieve the research objective, a Study Activity (EA) was constructed with four problems on basic numerical system five and base ten to allow a relationship between theory and practice around the mathematical object Decimal Numbering System (SND). The results suggest the expansion on the elements that constitute the NdS: count without grouping and by grouping, notion of numerals and numerical bases (nonpositional and positional), among others. It was also evidenced that the Workshop enabled collaborative actions, with discussions and socializations of productions, promoting the change of teaching practices and the deepening of knowledge.